The perversion of youth: controversies in the assessment and treatment of juvenile sex offenders - DiCataldo, Frank C. (Psychology and crime series, 2009)
The birth of a moral panic -- The return of the blob : the heterogeneity of juvenile sex offenders -- Test authors in search of a clinical population : risk assessment instruments for -- Juvenile sex offenders -- The adolescent as sexual deviant : the treatment of juvenile sex offenders -- Creating the objects of our concern : normal childhood sexuality and the -- Invention of childhood sexual behavior problems -- Becoming a man : the waiver of the juvenile sex offender to adult court -- Making monsters : the civil commitment of juvenile sex offenders -- Collateral consequences : the invisible punishment of the juvenile sex offender